Risk factors of pancreatic cancer and their possible uses in diagnostics - Lang, Jitka; Kunovský, Lumír; Kala, Zdeněk; Trna, Jan (Neoplasma, 2021)
Pancreatic cancer (PC) is a form of malignancy of increasing incidence and poor prognosis, with an average of less than 10% of patients surviving 5 years after being diagnosed. The main reason for this unfavorable situation is the long asymptomatic course of the disease, and the absence of a simple screening method, typically leading to the late discovery of the disease. The development of the malignancy from the initial carcinogenesis into invasive pancreatic carcinoma takes approximately 10 years. However, the progression of pancreatic cancer from early into advanced stages can be, according to the latest studies, incredibly fast, just a few months. Early stages of pancreatic malignancy can be detected only by expensive, and sometimes invasive, diagnostic methods (CT, MRI, or EUS). Due to the current absence of a reliable non-invasive screening method, it is necessary to define a group of patients who have the highest risk of PC development, five to ten times higher risk compared to the regular population at a minimum. Risk factors combine in their effect; therefore, relative risks of PC development need to be summarized to obtain a total relative risk for each person. The main and non-influenceable risk factor in the development of PC is the increasing age. The other non-influenceable risk factor of PC is a genetic predisposition - family incidence of the disease can be detected in 4-16% of patients. Some specific genes and mutations, which can play a role in PC development have already been identified (for example mutation of the PRSS-1 gene). Among the influenceable risk factors of PC is primarily smoking; obesity can play a part in PC development as well. A higher risk of PC is observed in patients with chronic pancreatitis. Nowadays, the relationship between PC and diabetes mellitus (DM) is hotly discussed. In the case of long-standing DM, the risk of pancreatic cancer is two times higher compared to the healthy population. However, new-onset DM can be the first sign of still asymptomatic PC. These patients, with paraneoplastic DM caused by pancreatic cancer cells, represent approximately 1% of recently diagnosed patients. However, this group of patients is still too large for screening. Because of that, it is necessary to find specific criteria to distinguish classic DM from the paraneoplastic form. The application of these criteria can help with the better stratification of risk in patients with new-onset diabetes and hence, it can help to discover PC in its early stages.
Keywords: rizikové faktory; Smoking; nádory slinivky břišní; Humans; kouření; lidé; Pancreatic Neoplasms; Genetic Predisposition to Disease; genetická predispozice k nemoci; Risk Factors